Modeling the start of the expansion due to alkali silica reaction in concrete - Gonzalez, L. (2011)
Service life of a concrete affected by alkali-silica reactions (ASR) is the age at which expansion is no longer allowed for normal use of a structure; such expansion level depends on the application. Once the induction period ends, the expansion proceeds quickly. Thus, in the present study, the service life was approached by the induction time. Induction time is an abstract concept, its formulation depending on the model considered (additive, constant time in the diffusion model, or the abscissa of intersection of time axis by a tangent to the expansion curve at the inflexion point, in the nucleation and growth model). Mortar bars were made with Tagus river reactive aggregate according the ASTM C 1260 procedure (expansion of bars immersed in NaOH 1M) implemented at temperatures of 80, 70, 60, 50 and 37ºC, to model expansion at constant alkalinity, considering the aggregate reactivity and temperature as variables. The results show that the data has enough precision for a kinetic study. Two kinetic models were considered to fit the data, selecting one of which for further improvement, using the wide information basis on the ASR. The effects of the factors temperature, alkalinity and humidity assumed models referred to in literature, or obtained by regression both of kinetic parameters for each isothermal curve and their temperature coefficients of Arrhenius plots. The correlations obtained allow estimating the strain after the induction period, for any value of the mentioned factors, under laboratory conditions. The model estimates at ca 37ºC were compared with experimental data in the same setup and this temperature. The induction time prediction was satisfactory, but further expansion development pattern was different. The model was tentatively applied to a case reported in literature. Results match, but are affected by significant errors, some improvements being referred to improve accuracy.